Extraction of Exact Solutions of Higher Order Sasa-Satsuma Equation in the Sense of Beta Derivative - Fadhal, Emad; Akbulut, Arzu; Kaplan, Melike; Awadalla, Muath; Abuasbeh, Kinda (MDPI AG, 2022)
Nearly every area of mathematics, natural, social, and engineering now includes research into finding exact answers to nonlinear fractional differential equations (NFDES). In order to discover the exact solutions to the higher order Sasa-Satsuma equation in the sense of the beta derivative, the paper will discuss the modified simple equation (MSE) and exponential rational function (ERF) approaches. In general, symmetry and travelling wave solutions of the Sasa-Satsuma equation have a common correlation with each other, thus we reduce equations from wave transformations to ordinary differential equations with the help of Lie symmetries. Actually, we can say that wave moves are symmetrical. The considered procedures are effective, accurate, simple, and straightforward to compute. In order to highlight the physical characteristics of the solutions, we also provide 2D and 3D plots of the results.
Keywords: beta derivative; sasa satsuma equation; wave transformations; exact solutions